2019
DOI: 10.1080/16522354.2019.1699764
|View full text |Cite
|
Sign up to set email alerts
|

Fluid institutional logics in digital journalism

Abstract: The negotiation of competing institutional logics is relevant for organisations active in multiinstitutional domains. News organisations are active in the domains of democracy and business, and, through digitisation, they are active in the digital technology domain. This article describes how journalism negotiates competing logics of these domains, i.e. professional, market, managerial, and technology (tech) logics. Analysing n = 744 individual NiemanLab Predictions for Journalism from 2014 to 2019, findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Professional and market logics have been traditionally compartmentalized in media organizations via the separation of editorial and business sides. Research has, however, shown that the two logics can become fused in, for example, audience-oriented journalism (Lischka, 2020).…”
Section: Institutional Logics and Journalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Professional and market logics have been traditionally compartmentalized in media organizations via the separation of editorial and business sides. Research has, however, shown that the two logics can become fused in, for example, audience-oriented journalism (Lischka, 2020).…”
Section: Institutional Logics and Journalismmentioning
confidence: 99%
“…Each institutional domain has a central logic that guides its organizing principles and provides actors with vocabulary of motive and identity (Thornton et al, 2012). Journalism can be conceptualized as a multi-domain constellation where logics arising from news organizations’ democratic-capitalist operating environment are multiple and often contradictory (Lischka, 2020). A classic example of conflicting logics is the clash between a professional logic, which is about journalism’s role as the fourth estate and its watchdog function over societal domains such as politics and the economy, and the market logic, which arises from media organizations’ need to treat news as a product to be sold for profit (Lischka, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the question of what constitutes quality journalism remains unanswered, with multiple understandings of the underlying assumptions (Waisbord, 2013). The divisive and evolving nature of journalistic identity has escalated through digitalization, as news organizations increasingly operate in a hybrid domain, negotiating between several competing and overlapping logics (Lischka, 2020). The contemporary journalistic logic is adopting to an “audience turn” (Zamith & Braun, 2019, p. 4), moving the focus towards the individual needs of audiences (Carlson, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beyond "liberal" bias, a novel source for delegitimation represents technological change (Tong 2018;Lischka 2020). In the digital environment, public service norms of journalistic knowledge production may not have changed, but the loss of epistemic authority can be ascribed to the loss of public spheres as journalism's sovereign territory.…”
Section: Journalism Legitimacymentioning
confidence: 99%